2008
DOI: 10.1021/ol802169j
|View full text |Cite
|
Sign up to set email alerts
|

An Ireland−Claisen Approach to β-Alkoxy α-Amino Acids

Abstract: A diastereoselective Ireland-Claisen approach to beta-alkoxy alpha-amino acid esters is reported. Amino acid esters of enol ethereal allylic alcohols undergo facile syn-selective [3,3]-sigmatropic rearrangement via silyl ketene acetals. Substrate synthesis, rearrangement development, stereoselectivity, and product elaboration are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…It has been reported that Ireland-Claisen rearrangement of esters derived from 3-alkoxyallylic alcohols display a substantial rate acceleration attributed to a vinylogous anomeric effect. [35] However, the stereochemical outcome of the rearrangement of propionates, [35] glycolates, [36] and glycinates [37] derived from acyclic 3-alkoxyallylic alcohols was similar to those observed with a regular allylic alcohol lacking a heteroatom at C3 and in agreement with the usual chairlike transition-state model (E to syn and Z to anti 1,2diastereoselectivity). [12] Only cyclic derivatives (3-hydroxy pyranoid and furanoid glycals) were found to rearrange preferentially through boat transition states.…”
Section: Sulfonamidesupporting
confidence: 66%
“…It has been reported that Ireland-Claisen rearrangement of esters derived from 3-alkoxyallylic alcohols display a substantial rate acceleration attributed to a vinylogous anomeric effect. [35] However, the stereochemical outcome of the rearrangement of propionates, [35] glycolates, [36] and glycinates [37] derived from acyclic 3-alkoxyallylic alcohols was similar to those observed with a regular allylic alcohol lacking a heteroatom at C3 and in agreement with the usual chairlike transition-state model (E to syn and Z to anti 1,2diastereoselectivity). [12] Only cyclic derivatives (3-hydroxy pyranoid and furanoid glycals) were found to rearrange preferentially through boat transition states.…”
Section: Sulfonamidesupporting
confidence: 66%
“…Similarly, sulfone derivative 7 was obtained in the presence of 2.2 equivalents of m ‐CPBA in CH 2 Cl 2 at room temperature over the course of 1 h (Scheme b) . Conversely, the reduction of 3 a with DIBAL‐H in toluene was achieved at −78 °C, and desired product 8 was obtained in 70 % yield (Scheme c) . Furthermore, the oxidation of 3 a with DDQ in a mixture of DCE/H 2 O or DCE/MeOH at room temperature afforded products 9 or 10 in yields of 45 or 79 %, respectively (Scheme d, e) .…”
Section: Resultsmentioning
confidence: 99%
“…[14] Conversely, the reduction of 3a with DIBAL-H in toluenew as achieved at À78 8C, and desired product 8 was obtained in 70 %y ield (Scheme 4c). [15] Furthermore, the oxidation of 3a with DDQ in am ixture of DCE/H 2 O or DCE/MeOH at room temperature afforded products 9 or 10 in yields of 45 or 79 %, respectively (Scheme 4d,e ). [16] Similar oxidation and reduction reactions were observed for 5a,a nd corresponding products 11, 12,a nd 13 were obtained in yields of 67-75 %( Scheme 5).…”
Section: Resultsmentioning
confidence: 99%
“…[12] Thec ore of rocaglamide is af ully substituted cyclopentane ring containing adjacent quaternary centers at the C3a and C8b positions.S tereochemical control, especially at the C3 position, has been ac hallenge for many of the previously published syntheses.E mbedded within the rocaglamide we perceived as tructure that we could access enantioselectively through aP d 0 -catalyzed Nazarov-type cyclization that we have recently developed. [14] Compound 3 was reacted with TMPMgCl·LiCl (TMP = 2,2,6,6-tetra- Known cinnamic acid (1) [13] was converted into acid chloride 2 by conventional means.E xposure of ethyl propiolate to 3,4-dimethoxybenzyl alcohol in dichloromethane at RT in the presence to DABCO (1,4-diazabicyclo[2.2.2]octane) produced vinylogous carbonate 3 in 82 %y ield.…”
mentioning
confidence: 99%